The experiential limits of the state: Territory and taxation in Garoowe, Puntland - Kirstine Strøh Varming (Danish Institute for International Studies (DIIS), 2017)
In this paper, I explore claims to "statehood" in the Somali federal member state of Puntland. Drawing on five months of ethnographic fieldwork in Puntland's capital Garoowe, I highlight the ways in which the Puntland administration appeals to a national political subjectivity in order to increase its tax base. Territorial discourses and conflicts play a central role in creating this political subjectivity and claim to "statehood". I argue that practices and discourses related to Puntland's territorial control contribute to the material, discursive and symbolic constitution of the state. Furthermore, I analyze the particular case of the Garoowe parking tax and the high levels of suspicion and rejection that emerged in reaction to it. This case demonstrates how state and municipal taxation and categorization of urban spaces (co-)produce the practical and experiential limits of state authority in contemporary Somalia and beyond.
Keywords: 330